METHODOLOGY OF ENSURING THE EFFICIENCY OF MECHANICAL PROCESSING DUE TO THE APPLICATION OF VIBRATION MONITORING AND VIBRATION PROTECTION MEANS - Nikolaevich, Gavrilin Alexey; Ivanovich, Odnokopylov Georgy; Grigorievich, Bukreev Viktor; Nikonova, Tatyana; Mikhailovna, Zharkevich Olga; Meirbekovna, Buzauova Toty (Journal of Applied Engineering Science, 2022)
The article describes the main causes and sources of impulse - vibration effects on the elements of the "machine tool – device - tool - detail" system. The paper deals with the development of methods for increasing the efficiency of machining due to the rational choice of technical solutions for vibration protection by design and technological methods with the use of vibration monitoring. A criterion for the efficiency of machining is given, which is determined by a matrix using scalar parameters, which are traditionally used for vibration diagnostics. A complex criterion for the quality of machining has been determined, which describes the indicators of the geometric accuracy of the machined surface. The block diagram of algorithms for selection and rational use of structural and technological methods of vibration protection of technological system elements is presented. Vibration and technological criteria for choosing solutions for vibration protection and monitoring are proposed. The implementation of the developed algorithms is considered on examples of machining and numerical estimates are given, confirming the high quality of the developed solutions.
Keywords: vibration protection, vibration diagnostics, machining, monitoring, efficiency, reliability